2020
DOI: 10.1016/j.jbusres.2020.05.058
|View full text |Cite
|
Sign up to set email alerts
|

What drives product-service integration? An abductive study of decision-makers’ motives and value strategies

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 81 publications
(176 reference statements)
1
26
0
Order By: Relevance
“…Lenka et al (2018a) showed how microfoundations can facilitate servitization transition by countering organizational resistance. Coreynen et al (2020) found that differences in decision-makers' motivationswhether they were driven by the need for achievement, affiliation or power - (Alghisi and Saccani, 2015), its implementation requires a revision of the entire organizational constitution (Vendrell-Herrero et al, 2017;Bustinza et al, 2018).…”
Section: Multilevel Perspective On Digital Servitizationmentioning
confidence: 99%
“…Lenka et al (2018a) showed how microfoundations can facilitate servitization transition by countering organizational resistance. Coreynen et al (2020) found that differences in decision-makers' motivationswhether they were driven by the need for achievement, affiliation or power - (Alghisi and Saccani, 2015), its implementation requires a revision of the entire organizational constitution (Vendrell-Herrero et al, 2017;Bustinza et al, 2018).…”
Section: Multilevel Perspective On Digital Servitizationmentioning
confidence: 99%
“…Only recently, the study of the microfoundations of servitization has begun to take shape. For example, Lenka et al [67] identified several tactics that individuals adopt to overcome organizational resistance, and Coreynen et al [68] explored what motives drive decision-makers to integrate products and services. However, as far as we know, no study has investigated the microfoundations of sustainable PSI.…”
Section: Overemphasis On the Firm Levelmentioning
confidence: 99%
“…Strategies-Regarding strategy, some prior studies have simply asked firms if they consider the integration of products and services important, and whether they have developed a strategy (or plan) for its implementation [49,68]. Others asked similar questions about product-service innovation [40,94], or they combined digital with green servitization strategy measures [10].…”
Section: The Firmmentioning
confidence: 99%
See 2 more Smart Citations